Attitude control precision analysis for hypersonic vehicles based on covariance analysis describing equation technique - Jianguo Guo (Advances in Mechanical Engineering, 2018)
This article investigates a control precision analysis based on covariance analysis describing equation technique for the generic hypersonic vehicle attitude tracking system. For a nominal generic hypersonic vehicle attitude system, a global sliding mode control strategy is pointed out first and then the stabilization of the control strategy is analyzed based on Lyapunov stability theory. In the presence of external disturbance moment and internal parameter perturbation, the statistical attitude model with the proposed control scheme is obtained using the covariance analysis describing equation technique. Moreover, 500 Monte Carlo tests are simulated for the hypersonic vehicle with the same disturbance and those mean and standard deviation are same as the results of the one-time covariance analysis describing equation technique simulation. Finally, the comparison of the covariance analysis describing equation technique and the Monte Carlo tests results shows that the covariance analysis describing equation technique is more effective and timesaving.